Whole genome sequence comparison of ten diagnostic brucellaphages propagated on two Brucella abortus hosts - Tevdoradze, Ekaterine; Farlow, Jason; Kotorashvili, Adam; Skhirtladze, Natia; Antadze, Irina; Gunia, Sophio; Balarjishvili, Nana; Kvachadze, Leila; Kutateladze, Mzia (Virology journal, 2015)
BACKGROUND: Recently the genome sequences of two brucellaphages, isolated in Georgia (Tb) and Mexico (Pr) were reported revealing pronounced sequence homogeneity and the presence of two major indels discriminating the two phages. Subsequent genome sequencing of six diagnostic brucellaphages: Tbilisi (Tb), Firenze (Fz), Weybridge (Wb), S708, Berkeley (Bk) and R/C phages identified three major genetic groups. However, the propensity for fine-scale genetic variability of diverse brucellaphages grown on multiple hosts within a single Brucella species remains unknown. METHODS: We sequenced the complete genomes of ten brucellaphages following initial propagation on B. abortus strain 141 and after subsequent propagation on B. abortus strain S19. All brucellaphages were isolated and propagated at the Eliava Institute including the original Tb phage. Genomic libraries were quantified using the Qbit and sheared on the Covaris M220. QC for fragmentation was performed on the BioAnalyzer 2100. DNA libraries were prepared using an Illumina Paired-End protocol and sequenced on the Illumina MiSeq. Sequence analysis was performed using Geneious and MEGA software. RESULTS: Comparative whole genome sequence analysis revealed genetic homogeneity consistent with previously published data as well as multiple nucleotide variations. Genomic changes as a result of passages were observed in similar genes and predominantly occurred at identical sites in separate phages. Multiple instances of within-sample genetic heterogeneity were observed often at shared genomics positions across phages. Positive selection was detected in the tail collar protein gene. We also identified a Staphylothermus marinus F1-like CRISPR spacer and sequences orthologous to both prophage antirepressors of Brucella spp. and intergenic sequences encoded by Ochrobactrum anthropi. CONCLUSION: We surveyed whole genome level diversity in phage lytic for B. abortus as they are propagated on alternate vaccine strains within the species. Our data extend previous results indicating select variable hotspots and broad genomic homogeneity as well as multiple common polymorphisms and within-sample variation. These data also provide additional genomes for future reference in comparative studies involving the molecular evolution and host specificity of brucellaphages.